The Role of Carbon Risk Perception, Accountant Behavioral Compliance and Sustainability Mindset on the Accuracy of Carbon Performance Reporting - Gusti Meinar Girda Ariani; Syahrani Syahrani; Maria Yovita R Pandin; Amiartuti Kusmaningtyas (Harmony Management: International Journal of Management Science and Business, 2025)
This study aims to analyze the development and scientific relationship between carbon risk perception, behavioral compliance of accountants, and sustainability mindset on the accuracy of carbon performance reporting through a bibliometric approach. This study is driven by the increasing need for accurate carbon reporting amidst global demands for sustainability transparency, as well as the limited understanding of the role of behavioral and psychological factors of accountants in ensuring the reliability of carbon reports. Research data was obtained from two leading scientific databases, namely Scopus and Google Scholar, with the main keywords "carbon risk perception," "behavioral compliance of accountants," "sustainability mindset," and "accuracy of carbon performance reporting." The data selection process was carried out using the PRISMA method to ensure the relevance and validity of the analyzed articles, while bibliometric analysis and visualization were performed using VOSviewer software. The results of the study indicate that the topic related to carbon reporting accuracy has evolved from a technical approach to a behavioral and psychological approach. Network and density visualizations show that behavioral compliance and sus-tainability mindset issues are still new but have high potential for development. Meanwhile, the authors' collaboration map demonstrates the geographic limitations of research, which remains concentrated in developed countries. These findings have important theoretical and practical implications, namely the need to integrate behavioral theory and professional ethics into sustainability accounting research and to en-hance accountants' capacity to understand carbon risks to ensure the accuracy of future sustainability re-porting.